HARI EFEKTIF MESIN KAPAL NELAYAN TRADISIONAL - Tambunan, Kaminton; Wasum, Wasum; Ali, Muklis (Riset Sains dan Teknologi Kelautan, 2025)
Ship engines are machines that play an important role in the dynamics of the fishing business. Unfortunately, traditional fishing boat engines in Indonesia are neglected in maintenance and repair, so that apart from affordable areas, efforts in unreached areas are very important. In this research, damaged machines are maintained and repaired, working hours are monitored, with the main aim of evaluating continued seaworthiness compared to machines that work continuously. Machine operation, machine working hours, assessed for one year in Tablolong village, East Nusa Tenggara, Indonesia. The effective day rate of operation ranges from 268±97 to 275±90 idle time in machine operation and from 190±175 to 200±165 idle time in continuous machine operation. Machines that are maintained every month have higher levels of operation and movement compared to machines that are maintained for three and five months. However, the seaworthiness of the engines is very low, mostly due to lack of understanding, unavailability of engine maintenance facilities. Effective days in machine operation were observed, during the period (January-November). Machine maintenance is very useful for traditional fishermen who lack skills. Nevertheless, ongoing long-term and systematic monitoring is necessary to have a greater understanding of maintenance and repair.